Pathomorphological Changes in Thiram Toxicosis in Broiler Chicken - Subapriya, S.; Vairamuthu, S.; Manohar, B. Murali; Balachandran, C. (International Journal of Poultry Science, 2007)
Thiram a fungicide used for treating corn and for storing food grains were incorporated at 15, 30 and 60 ppm into the toxin free diet of broiler chicken for four weeks from the day of hatch. The clinical signs were reduced weight gain, lameness, abnormal bending of the tibial bones, enlarged hock joints and sternal recumbency. Grossly tibial dyschondroplasia was seen as a white opaque unmineralized cartilage plug in the tibiotarsus. Histopathologically, tibiotarsus revealed thinning of the growth plate, irregular arrangement of the proliferating layer, abnormal thickening of the transitional layer and thickened hypertrophic layer in the thiram fed groups. Changes were also seen in the liver, bile duct, kidney, heart, crop, gizzard, intestine, lymphoid organs including bursa, spleen and caecal tonsils and brain. There was no mortality at any levels of thiram tested. Results of the present study thus revealed that thiram at a level of even 15 ppm affected the health and performance of broiler chicken.